3D displays - Lueder, Ernst 1932- (Wiley SID series in display technology., 2012)
This book addresses electrical engineers, physicists, designers of flat panel displays (FDPs), students and also scientists from other disciplines interested in understanding the various 3D technologies. A timely guide is provided to the present status of development in 3D display technologies, ready to be commercialized as well as to future technologies. Having presented the physiology of 3D perception, the book progresses to a detailed discussion of the five 3D technologies: stereoscopic and autostereoscopic displays; integral imaging; holography and volumetric displays, and:Introduces spati.